2019
DOI: 10.1021/acsami.8b20749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biomimicry in the Design of Osteoinductive Bone Substitutes: Nanoscale Matters

Abstract: Bone apatite consists in carbonated calcium deficient hydroxyapatite nanocrystals (CDHA). Biomimetic routes allow fabricating synthetic bone grafts that mimic biological apatite. In this work, we explored the role of two distinctive features of biomimetic apatites, namely nanocrystal morphology (plate vs. needle-like crystals) and carbonate content on the bone regeneration potential of CDHA scaffolds in an in vivo canine model. Both ectopic bone formation and scaffold degradation were drastically affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…The XPS analysis further verified that TCP phases only existed in NBC, illustrating that during the process of calcination the bovine bone might have decomposed into TCP and HA [30]. It has been reported that apatite in natural bone is a type of HA with an imperfect crystal structure, closer to that of calcium-deficient HA which has a Ca/P of about 1.5, similar to Ca/P in TCP [49, 50]. Moreover, it has been reported in the literature that, in vivo , NBC degrades and resolves faster than HA due to the high biodegradation rate and solubility of β-TCP [51].…”
Section: Discussionmentioning
confidence: 89%
“…The XPS analysis further verified that TCP phases only existed in NBC, illustrating that during the process of calcination the bovine bone might have decomposed into TCP and HA [30]. It has been reported that apatite in natural bone is a type of HA with an imperfect crystal structure, closer to that of calcium-deficient HA which has a Ca/P of about 1.5, similar to Ca/P in TCP [49, 50]. Moreover, it has been reported in the literature that, in vivo , NBC degrades and resolves faster than HA due to the high biodegradation rate and solubility of β-TCP [51].…”
Section: Discussionmentioning
confidence: 89%
“…TCP with ideal biocompatibility and osteoconductivity is a degradable ceramic that is rapidly absorbed and releases calcium and phosphate ions to induce bone formation in the body (Park et al, 2018). In recent studies, calcium phosphates obtained at low temperature had structural features and composition characteristics, which were much closer to the mineral phase of bone, and could enhance the osteoinductive and osteogenic properties (Barba et al, 2017, 2019). HA is the main component of human bone and accounts for approximately 70% (Holzwarth, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The same animal models are used for testing whether the scaffold architecture matters or not for the biological output. Data from implant testing and bone-specific animal models showed that, beyond chemical composition, the osteoinductive properties of bioceramic-based bone graft substitutes depend on gross architecture (e.g., 3D printing versus nanostructured scaffolds [217], the thickness and size of macropores [218], or the nanoarchitecture of the scaffold [219]). Osteoregeneration and biomechanical properties are improved by tailoring of pore sizes [220] or even adjusting the shape and distribution of HA crystals [221].…”
Section: Efficacy Evaluation Of Cap-based Bioceramicsmentioning
confidence: 99%